Sustainability and higher education: analysis of shares of sustainability of two institutions of higher education Santa Catarina - Pontes, Andrea Simone Machiavelli; Carneiro, Caroline; Petry, David Rodrigo; Pilatti, Citania Aparecida; Sehnem, Simone (Revista de Administração da UFSM, 2015)
This qualitative and descriptive study, aims to understand the concepts of sustainability and identify how they are included in the action planning of Higher Education Institutions (HEI) of Santa Catarina. Therefore, a brief literature review on the topic of sustainability was held and on the relationship of sustainability with education and later with the HEI. The problem of this study consists in identify how the surveyed HEIs are inserting sustainability in a practical way, in the institution´s activities. The disclosed results showed that HEI adopt attitudes that meet the global context, both in its institutional actions, including the practice of the courses offered to its target audience, and in its image in the community. Thus, through the printed documents analysis and information available in the corporate website of the HEIs studied - National Service of Commercial Education (SENAC/SC) and Educational Society of Santa Catarina (SOCIESC), it was possible to identify that both organizations adopt actions and practices for the inclusion of sustainability in its institutional activities, which responds readily to the general purpose of this study.